2006
DOI: 10.1016/j.finmar.2006.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Order book characteristics and the volume–volatility relation: Empirical evidence from a limit order market

Abstract: Using unique data, we address the issue of price formation in a limit order market. A standard volume-volatility relation is documented with the number of trades acting as the important component of volume. The main contribution of the paper is to identify strong evidence that volume, volatility, and the volume-volatility relation are negatively related to the order book slope. These results are robust to the inclusion of several liquidity measures. A significant empirical relationship between the order book s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(16 citation statements)
references
References 18 publications
(6 reference statements)
1
15
0
Order By: Relevance
“…Joulin et al [63] analyzed the one-minute data of 163 USA stocks and found that news and trading volume play a minor role in causing large price changes, which is thus conjectured to be caused by the vanishing of liquidity. Naes and Skjeltorp [64] studied the order flow data from the Oslo Stock Exchange in Norway and found that price fluctuations are positively correlated with trade number, a component of trading volume, and negatively correlated with different liquidity measures.…”
Section: Introductionmentioning
confidence: 99%
“…Joulin et al [63] analyzed the one-minute data of 163 USA stocks and found that news and trading volume play a minor role in causing large price changes, which is thus conjectured to be caused by the vanishing of liquidity. Naes and Skjeltorp [64] studied the order flow data from the Oslo Stock Exchange in Norway and found that price fluctuations are positively correlated with trade number, a component of trading volume, and negatively correlated with different liquidity measures.…”
Section: Introductionmentioning
confidence: 99%
“…Almgren and Lorenz () explain price momentum by modeling Brownian motion with a drift whose distribution is updated based on Bayesian inference. Næs and Skjeltorp () show that the order book slope measures the elasticity of supplied quantity as a function of asset prices related to volatility, trading activity, and an asset's dispersion beliefs.…”
Section: Machine Learning For Hft and Lobmentioning
confidence: 99%
“…We believe the new approach is universal and can be applied to other fields where a proper assessment of the relative amount of signal variation is critical (e.g. financial markets [33][34][35] , or neuroscience 36,37 ). Additionally, the number of sources annotated by political bias was relatively low and skewed towards the US which significantly decreased the reliability and generality of the results, although giving a more homogeneous dataset to analyze.…”
Section: Discussionmentioning
confidence: 99%